Understanding performance analysis for front wheel drive (FF) sedan vehicle under steady and ride road driving condition - Muhammad Faizul Izreen, Othman (2010)
Research in the area of vehicle dynamics in the on-road skidding condition is limited. The used methods generally are using simulation that the environmental elements that influence the vehicle dynamics were ignored. The skidding condition is the influences factors in handling the vehicle and user safety in order to achieve the safe and controllable maneuver. The driver input and the responses in the skidding condition have a limitation and range to have a safe maneuver. The purpose of this research is to analyze the yaw stability in the understeer condition. To perform an investigation ofundersteer performances in the real maneuver, the experiment that considered all the noise from the surrounding that influence the vehicle has been done. The steady state cornering, lane change, and straight line braking experiment was used to determine the relationship between side slip angle and slip angle. Persona 1.6 (MT) equipped with the RV-4 vector sensor, Gyroscopic sensor with DEWEtron Data acquisition system was used as the test car and the apparatus for this experiment. Result obtains from the experiment verified the vehicle stability in the understeer condition being achieve between the theoretical and experimental data.